Writing desk at Discove Cottage - David Laws:::Creator::::::::::::
Steinbeck's writing desk at Discove Cottage, Somerset, England. John and Elaine Steinbeck lived in the Cottage while he worked on his "reduction of Thomas Malory's Morte d'Arthur to simple readable prose without adding or taking away anything" Digital copy only. No hard copy.